Variabilidade de caracteres bioagronômicos na seleção de porta-enxertos de pessegueiro. - Schmitz, Juliano Dutra (2011)
In the production of any fruit tree species, quality of the seedings, the knowledge of the best combinations of rootstock and scion in different climate and soil conditions, are crucial for the success of productive orchard. Thus, the use of rootstocks with good agronomic traits in peach is very important for achieving success in the production. The present study aimed at assessing the variability of morphological traits of seedlings of rootstocks in three cropping systems (field, plastic bags on benches in an open environment, and greenhouse plastic cover and shade in plastic bags on benches) conditions nursery trade. Additionally, we investigated the vigor and productivity of peach Chimarrita cultivar grafted on different rootstocks by bioagronomics variability of characters in the sixth and seventh year after the implementation of the orchard, growing conditions in the region of Pelotas / RS. Therefore two experiments were conducted. Experiment 1 - was conducted in a commercial nursery in Pelotas - from July 2010 to January 2011. We evaluated the percentage of emergence and development of seedlings of Capdeboscq and 'Okinawa' - including from seeding to the period after grafting. It was concluded that: The percentage of emergency rootstocks 'Okinawa' and Capdeboscq is influenced by genotype and the environment where it is performed sowing, higher for Capdeboscq , regarding the 'Okinawa', and more fullyfield independent of the genotype used, independent of cropping system, Capdeboscq presents greater trunk diameter at the time of grafting, in comparison to 'Okinawa'; It is possible to obtain seedlings of 'Okinawa' and Capdeboscq with fewer side branches when planting is done in plastic bags on benches in a greenhouse with plastic sheeting; Regardless of 9 the rootstock, the Chimarrita has the highest percentage of grafts sprouted and the average length of the regeneration of the graft in the growing field: The effect of seedling peach nursery is greater when using Capdeboscq as rootstock in relation to the use of 'Okinawa'. Experiment 2 was conducted in an orchard the scion 'Chimarrita' (six years) grafted on the rootstock 'GF 305', 'Tsukuba1' and 'Okinawa', as in traditional scion cultivars Capdeboscq and 'Aldrighi'. The present study concludes that: The Chimarrita showed balance in vigour regardless of the rootstock used; Rootstocks 'Tsukuba 1' and 'Okinawa' show is adapted and productive in Pelotas, RS; Use different rootstocks in 'Chimarrita' does not alter the firmness and total soluble solids; Productive efficiency is a parameter that can be used for the selection of rootstocks for peach for vigour.